A holistic ecological approach to sport and study: The case of an athlete friendly university in Denmark. (March 2020) - Henriksen, Kristoffer; Storm, Louise Kamuk; Kuettel, Andreas; Linnér, Lukas; Stambulova, Natalia
Abstract: Objectives: Dual career development environments (DCDEs) exist to support student-athletes in their endeavours to combine sport with education or work. Such environments are likely to vary in their structure, processes, philosophy, and degree of efficiency. With the overall aim of applying the holistic ecological approach (Henriksen, Stambulova & Roessler, 2010) to the study of DCDEs, the objectives of the present study are: (a) to provide a holistic description of a Danish athlete-friendly university as a DCDE, and (b) to investigate the factors influencing the environment's effectiveness. Methodology: Based on two working models, the study takes a case study approach and a real-time perspective and uses multiple sources of data (interviews, observations, and documents). Results: Two empirical models summarize the findings and portray the DCDE as: (1) centred on a dual career (DC) support team that serves to support communication and coordination between the sport, study, and private domains; (2) focused on providing individual solutions for each athlete; (3) teaching student-athletes to plan, prioritize, communicate, and take responsibility for the balance in their DC endeavour; and (4) deeply rooted in a shared DC philosophy that puts sport first and recognizes that the student-athletes must be seen as whole persons. Conclusion: Researcher-practitioners in the DC context are encouraged to focus not only on the challenges and coping strategies of the individual student-athletes but to understand and (if necessary) optimize the entire environment around them. Highlights: This study is a part of the Erasmus + Sports project "Ecology of Dual Career". It applies the holistic ecological approach to the study of dual careers. It introduces the dual career development environment (DCDE) and two working models. Explores a Danish university DCDE by transforming working models to empirical models. Stimulates readers to consider the role of environment in athletes' dual careers.